(untitled) (Research, Society and Development, 2020)
The occurrence of impacted lower canines is not commonly observed in dental clinical practice. Several treatment options might be proposed for these cases. This paper aims to report the surgical treatment of an included canine in the base of the mandible. This is a 13-year-old male patient who sought orthodontic treatment aiming dental alignment due to the presence of non-exfoliated deciduous canine. With the aid of panoramic radiography and computed tomography, it was observed the horizontal position of the right lower canine included, as well the advanced stage of root formation of the tooth in question. There was also a radiolucent image involving the crown of the same tooth, suggesting cystic lesion. These conditions showed the impossibility of orthodontic treatment for repositioning the permanent canine in the lower arch. Thus, the planning and surgical treatment were performed with great precision. No trans and postoperative complications were observed. From the data obtained in the literature and by analyzing the case in question clinically and radiographically, the most viable treatment in this case was the surgical removal of the canine.